Comparative neurobiology of vigilance and stress adaptation systems in wild and laboratory rodents (Rattus norvegicus) - Kent, Molly; Crockett, Brendan; Narayanan, Aditya; Dilandro, Isabel; Wagner, Ava; Mauco, Andrés; Handford, Gabriella; Luby, Paean; Hunter, Richard; Richter, Troy; Richardson, Jonathan; Harding, Olivia; et al. (Frontiers in Ethology, 2025)
Although chronic stress is typically associated with disease and negative outcomes, wild animals often survive—and even thrive—in environments marked by recurring threats. In this study, we investigated neurobiological differences in vigilance-associated and stress-coping systems, as well as resilience, in wild and laboratory-bred rats (Rattus norvegicus) to explore potential survival-related adaptations in wild populations. Consistent with previous findings, wild rats exposed to chronic environmental stressors exhibited heightened hypothalamic-pituitary-adrenal axis activity, evidenced by enlarged adrenal glands and elevated fecal metabolites of glucocorticoids. Brains were processed using thionin staining for neural and glial cell counts and immunohistochemistry for immunoreactive targets. Wild rats exhibited neuronal and glial cell modifications in vigilance-related cortical regions, including the auditory and piriform cortices. Additional adaptations included increased glial cell density in the lateral habenula—a region implicated in coping appraisal—and enhanced microvascular density in the hippocampus. These findings underscore the value of incorporating wild animals exposed to naturalistic stressors into the study of adaptive and maladaptive stress responses. Integrating wild and laboratory models may yield translational insights for developing therapeutic strategies targeting stress- and anxiety-related disorders.